PKM PENERAPAN SISTEM PEMBELAJARAN DALAM JARINGAN (SPADA) SEBAGAI ALTERNATIF PEMBELAJARAN JARAK JAUH PADA SMAN 1 PAGELARAN - Agus Wantoro (UPPM Politeknik Gorontalo, 2022)
PKM activities were carried out at SMAN1 Pagelaran, Pringsewu Regency, Lampung Province. The PKM material presented was providing training on the use of a networked learning system (SPADA) in implementing distance learning. SPADA developed using LMS standards that have been determined, namely in the learning content section in each session and evaluation standards for school management. The results of the evaluation of learning understanding using a questionnaire in the form of a questionnaire given to 25 PKM participants obtained a fairly good score in the form of participants' understanding of learning management using online media